A Development of English for Local Tourism Instructional Model in Nakhon Ratchasima Province - Lornklang, Thanachart (Ratchaphruek Journal, 2021)
An English for local tourism instructional model in Nakhon Ratchasima province was developed to enhance students’ English oral communication ability using a research and development methodology. The purposes of this research were; 1) to develop an English for local tourism instructional model in Nakhon Ratchasima Province, and 2) to evaluate the quality of the developed instructional model. The research procedure was divided into 3 phases: 1) develop the English for local tourism instructional model in Nakhon Ratchasima Province; 2) construct the research instruments, and 3) evaluate the quality of the developed instructional model by implementing it with 36-undergraduate students who were enrolled in English for local tourism in the first semester of the academic year 2018 at Nakhon Ratchasima Rajabhat University. The samples were selected using cluster random sampling. The research instruments were the oral communication ability test, local attraction knowledge test, and learner’s log. The data were analyzed using a t-test. The findings of this study were: 1) The teaching stages of English for the local tourism instructional model were: Orientation, Preparation, Information gathering, Project presentation, and Wrap-up,and 2) The evaluation of the English for local tourism instructional model revealed that after taking the developed instructional model, the post-test mean scores of the students’ English oral communication ability and their local attraction knowledge were significantly higher than their pre-test ones at the level of .05. The developed instructional model could improve students’ English oral communication ability and their local attraction knowledge. The research results can be applied to create other instructional models, lessons, and learning procedures in the tourism context.